Effect of enzalutamide on PK of P‐gp and BCRP substrates in cancer patients: CYP450 induction may not always predict overall effect on transporters - Srinivasu Poondru; Vitalii Ghicavii; Reza Khosravan; Pooja Manchandani; Nakyo Heo; Selina Moy; Tomasz Wojtkowski; Melanie Patton; Gabriel P. Haas (Wiley, 2022)
Abstract Drug‐drug interaction (DDI) is an important consideration for clinical decision making in prostate cancer treatment. The objective of this study was to evaluate the effect of enzalutamide, an oral androgen receptor inhibitor, on the pharmacokinetics (PK) of digoxin (P‐glycoprotein [P‐gp] probe substrate) and rosuvastatin (breast cancer resistance protein [BCRP] probe substrate) in men with metastatic castration‐resistant prostate cancer (mCRPC). This was a phase I, open‐label, fixed‐sequence, crossover study (NCT04094519). Eligible men with mCRPC received a single dose of transporter probe cocktail containing 0.25 mg digoxin and 10 mg rosuvastatin plus enzalutamide placebo‐to‐match on day 1. On day 8, patients started 160 mg enzalutamide once daily through day 71. On day 64, patients also received a single dose of the cocktail. The primary end points were digoxin and rosuvastatin plasma maximum concentration (Cmax), area under the concentration‐time curve from the time of dosing to the last measurable concentration (AUClast), and AUC from the time of dosing extrapolated to time infinity (AUCinf). Secondary end points were enzalutamide and N‐desmethyl enzalutamide (metabolite) plasma Cmax, AUC during a dosing interval, where tau is the length of the dosing interval (AUCtau), and concentration immediately prior to dosing at multiple dosing (Ctrough). When administered with enzalutamide, there was a 17% increase in Cmax, 29% increase in AUClast, and 33% increase in AUCinf of plasma digoxin compared to digoxin alone, indicating that enzalutamide is a "mild" inhibitor of P‐gp. No PK interaction was observed between enzalutamide and rosuvastatin (BCRP probe substrate). The PK of enzalutamide and N‐desmethyl enzalutamide were in agreement with previously reported data. The potential for transporter‐mediated DDI between enzalutamide and digoxin and rosuvastatin is low in men with prostate cancer. Therefore, concomitant administration of enzalutamide with medications that are substrates for P‐gp and BCRP does not require dose adjustment in this patient population.